Physiological and genetic determination of yield and yield components in a bread wheat × spelt mapping population - Xie, Quan (2015)
A substantial increase in wheat yield is needed for global food security. This requires a comprehensive understanding of the physiological and genetic basis of yield determination. The present study aimed to dissect yield physiologically and genetically in a recombinant inbred line mapping population derived from bread wheat × spelt. A total of 201 traits were investigated in the field and glasshouse across three years, and these traits formed five themes: genetic variation in yield and yield components, and the usefulness of spelt as a genetic resource; tillering dynamics; biomass accumulation; flowering time and subsequent leaf senescence; and grain filling processes. Large genetic variation in all traits was found, and spelt showed many desirable traits and alleles independent of low threshability, so it can be used to broaden genetic diversity for yield improvement in bread wheat, while maintaining the free-threshing habit. Quantitative trait loci for tiller production and survival were identified, which were also affected by light environment under the canopy: low red:far red ratio (R:FR) led to early tillering cessation, few total shoots, high infertile shoot number and shoot abortion, probably resulting from an assimilate shortage due to early and enhanced stem growth induced by low R:FR. More fertile tillers normally contributed to plant yield and grain number, but reduced individual grain weight, partly because of smaller carpels and fewer stem water soluble carbohydrates at anthesis. In addition, preanthesis biomass accumulation increased yield and yield components. For grain weight, slightly early anthesis and delayed but fast leaf senescence were associated with larger grains. Carpel size at anthesis, grain dry matter and water accumulation, as well as grain morphological expansion, determined final grain weight, because of pleiotropy or tight gene linkages. These findings provide deeper insight into yield determination in wheat, and facilitate trait-based physiological and molecular breeding.